Portable means of cryptographic protection of sensitive data - Евсеев, Сергей Петрович; Король, Ольга Григорьевна (Bulletin of National Technical University "KhPI". Series: System Analysis, Control and Information Technologies, 2013)
The main demands made to the hardware and software tools for protecting sensitive data, a comparative analysis of the main features of portable hardware data protection category USB flash drives.